1990
DOI: 10.1165/ajrcmb/2.4.381
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Response to Silica or Titanium Dioxide: Inflammatory Cells, Alveolar Macrophage-derived Cytokines, and Histopathology

Abstract: We investigated the effects of silica (SiO2) and titanium dioxide (TiO2) on the pulmonary recruitment of inflammatory cells and the ability of alveolar macrophages (AMs) to release the pro-inflammatory cytokines, interleukin 1 (IL-1) and tumor necrosis factor alpha (TNF). Rats were intratracheally instilled with 5 to 100 mg/kg of the materials, and bronchoalveolar lavage cell populations and AM cytokine release were characterized on days 1, 7, 14, and 28. Both dusts elicited dose-related increases in neutrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
114
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(121 citation statements)
references
References 31 publications
7
114
0
Order By: Relevance
“…Among the cytokines secreted following phagocytosis of silica particles, TNF-␣ has been shown to play a critical role in the pathogenesis of silicosis (15,42), and actions that antagonize the biological effects of TNF-␣ ameliorate silica-induced fibrosis in mice (46,47). TNF-␣ may also be necessary for the expression of other more downstream growth factors and the consequent development of fibrosis (54,55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the cytokines secreted following phagocytosis of silica particles, TNF-␣ has been shown to play a critical role in the pathogenesis of silicosis (15,42), and actions that antagonize the biological effects of TNF-␣ ameliorate silica-induced fibrosis in mice (46,47). TNF-␣ may also be necessary for the expression of other more downstream growth factors and the consequent development of fibrosis (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…In the lung, the alveolar macrophage (AM) is primarily responsible for the binding, ingestion, and clearance of inhaled particulate matter (15). The AM response to inhaled particulates ranges from ingestion and clearance with minimal inflammation to profuse production of inflammatory cytokines and reactive oxygen intermediates (1,10,61).…”
mentioning
confidence: 99%
“…the dose and type of silica used and the mode of silica instillation. With regard to the dose, Driscoll et al (1) showed that silica stimulation of TNF␣ release occurred only at doses greater than 50 mg/kg. Lemaire (26) also reported the lack of silica effect on TNF␣ release at a low silica dose of 15 mg/kg.…”
Section: Figmentioning
confidence: 99%
“…Tumor necrosis factor-␣ (TNF␣) 1 is a macrophage-derived peptide that has been shown to play an important role in the pathogenesis of pulmonary fibrosis (1)(2)(3). Several fibrogenic agents such as crystalline silica and asbestos stimulate TNF␣ mRNA expression and protein synthesis in macrophages (2,3).…”
mentioning
confidence: 99%
“…Apart from acting as the primary nonspecific defense of the lung against inhaled PM, alveolar macrophages modulate the inflammatory response by secreting various mediators [10][11][12][13]. Oxidative stress may underlie the adverse health effects of many inhaled pollutants [14,15].…”
Section: Introductionmentioning
confidence: 99%